Correlation between total suspended particles and natural radionuclide in Malaysia maritime air during haze event in June-July 2009 - Sabuti, Asnor Azrin; Mohamed, Che Abd Rahim (Zibeline International Publishing, 2018)
Atmospheric particles in the surface air including aerosol and dust were collected using high volume air sampler (HVAS) for obtaining the activity levels of 210Pb and 210Po over Malaysian waters during the EPSP’09 Scientific Expedition. The average mass concentration of total suspended particles (TSP) in maritime air was 33 ± 2 μg/m3 (ranged from 13 ± 1 to 74 ± 4 μg/m3). Based on previous literatures, it has been suspected that the haze episodes were mainly due to forest and peat bog fires as well as vehicle and industrial emissions during dry period, especially during southwest monsoon. Consequently, the activity levels of 210Pb and 210Po in maritime particles were relatively in proportion with the TSP concentrations. Meanwhile, the temporal variation of 210Po/210Pb activity ratios in the aerosol samples perhaps related to the difference of residence time airborne particles and contribution from different sources of radionuclides in which 210Pb and 210Po are not in secular equilibrium. The highest TSP concentrations and 210Pb and 210Po activities were closely related to warm and dry period during southwest monsoon.